Ductility and Toughness of Unsymmetrical CFRP Strengthening of Reinforced Concrete Beams - M. Njeman, Abdulsalam; S. Mahmoud, Akram (Iraqi Journal of Civil Engineering, 2018)
The use of externally bonded composite materials such as carbon fiber reinforced polymers (CFRP) sheets is a modern and convenient way for strengthening and repairing reinforced concrete (RC) beams. This study presents experimental investigations on the flexural behavior of reinforced concrete beams strengthened by unsymmetrical CFRP sheets with various configurations. Effects of number of which strengthened faces of strengthening and fiber direction on the flexural strength of RC beams are examined. Six RC beams with dimensions of 100 mm * 220 mm were casted and tested under two points loading. One beam considered as a reference (unstrengthened) beam. Five residual beams were strengthened using CFRP sheets with various configurations. From the results, it was observed that all strengthened beams showed higher ultimate load capacity than that of the control beam. On the other hand, it was found that a progressive reduction in flexural ductility and toughness of beams with strengthening in one face and two faces with horizontal fiber direction. The highest decrease in flexural ductility and toughness for strengthened beams with horizontal fiber direction in comparison to control beam were 63% and 54%, respectively. On the contrary, the flexural ductility and toughness of strengthened beams increased with strengthening by vertical fiber direction. Additionally, the maximum percentage of increase in flexural ductility and toughness were 41% and 54%, respectively in comparison with control beam.